2015
DOI: 10.1071/zo14024
|View full text |Cite
|
Sign up to set email alerts
|

Cats (Felis catus) are more abundant and are the dominant predator of woylies (Bettongia penicillata) after sustained fox (Vulpes vulpes) control

Abstract: The control of foxes (Vulpes vulpes) is a key component of many fauna recovery programs in Australia. A question crucial to the success of these programs is how fox control influences feral cat abundance and subsequently affects predation upon native fauna. Historically, this question has been difficult to address because invasive predators are typically challenging to monitor. Here, non-invasive DNA analysis was used to determine the fate of radio-collared woylies (Bettongia penicillata) in two reserves in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 57 publications
2
78
0
Order By: Relevance
“…Selectively removing predators from invaded ecosystems can have undesirable consequences through the release of their introduced prey (Bergstrom et al, 2009) or other introduced predators (Marlow et al, 2015;Norbury et al, 2013;Rayner et al, 2007). Management of a single species, without regard for its flow-on effects on other species, may result in ecological surprises and unintended consequences.…”
Section: Integrated Multi-species Pest Managementmentioning
confidence: 98%
See 2 more Smart Citations
“…Selectively removing predators from invaded ecosystems can have undesirable consequences through the release of their introduced prey (Bergstrom et al, 2009) or other introduced predators (Marlow et al, 2015;Norbury et al, 2013;Rayner et al, 2007). Management of a single species, without regard for its flow-on effects on other species, may result in ecological surprises and unintended consequences.…”
Section: Integrated Multi-species Pest Managementmentioning
confidence: 98%
“…Potgieter et al, 2013). If lethal control is used, it should be applied using whole-of-ecosystem approaches to prevent unexpected and undesirable outcomes (Colman et al, 2014;Marlow et al, 2015;Norbury et al, 2013;Ruscoe et al, 2011).…”
Section: Integrated Multi-species Pest Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in northern Australia, recent research has indicated that predation by feral cats has greater impact in areas exposed to more frequent and/or extensive fires (McGregor et al 2014). In south-western Australia, concerted management action has led to some benefit through reduction in the abundance of the European red fox, but that change in abundance has now led to increased impacts of predation by feral cats (Marlow et al 2015). Many species now face multiple threats: for example, the koala Phascolarctos cinereus is affected by disease (including Chlamydia and a retrovirus), predation by feral (and stray) dogs, timber harvesting, changed fire regimes, road traffic, habitat loss and fragmentation, drought and days of extreme heat.…”
Section: Resultsmentioning
confidence: 99%
“…The most notable exclusion is feral cats (Felis catus), a predator of bilbies, whose populations are thought to strongly interact with targeted fox baiting (Marlow et al 2015). In a system with both foxes and cats, a resultant release of cats after fox control might strongly influence conservation outcomes for bilbies for a given baiting schedule.…”
Section: Limitationsmentioning
confidence: 99%